Computer vision syndrome and its associated factors in health science students from a university in Peru - Lopez-Choquegonza, Rocío; Copaja-Corzo, Cesar; Flores-Cohaila, Javier (Frontiers in Public Health, 2025)
The objective was to estimate the prevalence and identify the factors associated with Computer Vision Syndrome (CVS) among health science students at a university in Peru, we conducted a cross-sectional analytical study in Tacna, Peru, from October 12 to December 15, 2023. Participants were assessed through physical surveys. We evaluated 502 health science students; 59.2% were female, and the median age was 21 years (range 19 to 23 years). 78.1% had CVS, and 52% had moderate nomophobia. In the adjusted model, monthly family income of 2000 to 5,000 soles (PR: 0.81; 95% CI: 0.73 to 0.91) and over 5,000 soles (PR: 0.84; 95% CI: 0.74 to 0.95) was associated with a lower prevalence of CVS compared to families with income less than 2000 soles. Additionally, the prevalence of CVS was higher among students with moderate nomophobia (PR: 1.91; 95% CI: 1.24–3.16) and severe nomophobia (PR: 2.07; 95% CI: 1.31–3.48) compared to those with no symptoms or only mild symptoms of nomophobia. The prevalence of CVS is high among health science students, especially in medical students. As the severity of nomophobia increases, so does the prevalence of CVS, and higher family income is associated with lower CVS.